Pengembangan Perangkat Pembelajaran Berbasis Keterampilan Proses pada Materi Ekosistem Kelas X Biologi SMA Negeri 11 Enrekang - Norma Norma; Anatjhe Lihiang; Dientje F. Pendong (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research aims to develop learning tools based on science process skills on ecosystem materials at SMA Negeri 11 Enrekang. The research focuses on creating teaching modules and learner worksheets (LKPD) that can increase students' understanding and active involvement in biology learning. This study uses a 4-D development model consisting of four stages: definition, design, development, and deployment, with this research limited to the development stage. The methodology used involves analyzing the needs of students and teachers, designing learning tools, and testing the validity and practicality of the developed tools. The validity test involved two expert validators, while the practicality test was carried out by involving teachers at SMA Negeri 11 Enrekang. The assessment is carried out through a questionnaire that measures the validity and practicality of the learning tools. The results showed that the learning tools developed received an excellent validity assessment, with a "very valid" score for the teaching module and "valid" for the LKPD. The practicality test also showed positive results, with the learning tools rated "very practical" by teachers. These findings indicate that science process skills-based learning tools effectively improve students' understanding of ecosystem materials. This research significantly contributes to developing process skills-based learning tools, which can be adapted in other schools. Further research could test the applicability of these devices to other materials and in different schools to expand their application in biology learning.